2016
DOI: 10.1139/cjps-2015-0245
|View full text |Cite
|
Sign up to set email alerts
|

Reed canarygrass crop biomass and silage as affected by harvest date and nitrogen fertilization

Abstract: Reed canarygrass (Phalaris arundinacea L.) is a potential biomass crop for energy production but little is known on its optimum management in the northern areas of North America. We determined the effect of three harvest dates (late July, early September, and mid-October) in a one-cut system and four N fertilization (0, 40, 80, and 160

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Nutrient addition can enhance plant biomass and development [ 41 , 42 ]. Our results demonstrated that nutrient addition had a significant positive effect on leaf mass, number of ramets, and height of P .…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient addition can enhance plant biomass and development [ 41 , 42 ]. Our results demonstrated that nutrient addition had a significant positive effect on leaf mass, number of ramets, and height of P .…”
Section: Discussionmentioning
confidence: 99%
“…This result confirms the greater response of forage N concentration to N application rates in the second and third post-seeding years than in the first post-seeding year, and the greater benefits of applying N when the contribution of the legume species to forage DM yield is less than 30%. Increases in N concentration of forage grasses with increasing N fertilization have often been reported in eastern Canada (Tremblay et al 2005;Pelletier et al 2009;Bélanger et al 2016).…”
Section: Forage Nutritive Value N Concentrationmentioning
confidence: 95%
“…This result confirms the greater negative response of forage NSC concentration to N application rates in the second and third post-seeding years than in the first post-seeding year. Both negative effect (Tremblay et al 2005;Bélanger et al 2016) or no effect (Pelletier et al 2009) of increasing N fertilization on NSC or WSC concentration of forage grasses have been reported.…”
Section: Sitementioning
confidence: 99%
“…However, Himken et al (1997) (Wrobell et al, 2008) and seed retention (Wrobell et al, 2009). Suitable conditions for RCG growing as an energy plant are also in North America in areas with less than 1700 growing degreedays (5 °C basis) (Bélanger et al, 2016).…”
Section: Cultivation Areamentioning
confidence: 99%